Distribution and relative abundance of pig breeds in South-Western Agro-ecological Zone, Uganda: Status of locally adapted pigs - Kampire, Jackline; Rugunda, Kagoro Grace; Kiwanuka, Gertrude N. (Status of locally adapted pigs, 2023)
A cross-sectional study was conducted in five districts in South Western Agro-Ecological Zone (SWAEZ), Uganda, to map pig breed distribution and determine their abundance and population structure. Purposive and snowball sampling methods were used to identify pig farmers whose pigs were included in the study. Pig breeds were identified using the NAADS user guide on pig husbandry. The breeds that were properly identified in the study districts included Camborough, Landrace, and Large White; crosses and locally adapted pig populations were not differentiated into specific breeds. Camborough breed was the least abundant (0.69%), Landrace (5.0%), Large white (15.75%), crosses constituted 23.35% and majority of the pigs (55.2%) belonged to the non-descript locally adapted ecotypes. Piglets (36.82%), constituted the highest percentage to the total pig population followed by females (30.22%), growing females (15%), growing males (11%) and the least were adult males (6.89%). More farms kept the locally adapted populations (56.5%) compared to those with the other breed types, all combined and majority of the farms were owned by females (63.22%). Herd size ranged from 1 to 3 pigs at any given time. Exotic breeds and or crossbreds were kept in big numbers while the locally adapted pigs were few per household; 20.1% of the farms had only one pig. Tethering was the most used type of holding at the farms (62.55%). Exotic breeds have penetrated the rural areas and are very abundant. Locally adapted ecotypes are therefore threatened by continued crossbreeding for breed improvement and introduction of new breeds. Farms keeping locally adapted pigs can be facilitated to increase their herd sizes for profitable projects instead of changing breeds. New breed introduction and promotion should be regulated and monitored.
Keywords: Pig breeds; Distribution; Abundance; Southwestern Agro-ecological zone